Thermal behaviour of polylactic acid (PLA) nanocomposite based on modified nanoclay - Nur Madieha, Md Yusof (2012)
Polylactic acid(PLA)has attracted much attention due to their biodegradability and biocompatibility properties. The organically modified montmorillonite or known as nanoclay namely Cloisite B30 (the montmorillonite modified with a quaternary ammonium salt) was used in this research. PLA nanocomposite was prepared by melt intercalation method. Morphological,thermal and mechanical analysis was investigated for both pristine PLA and PLA organoclay nanocomposite.The morphological analysis was observed using both X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). Thermal stability for the nanocomposites were studied using Thermogravimetric Analysis (TGA). Glass transition temperature, T data has been collected and analyzed using Differential Scanning Calorimeter (DSC). Other than that,the mechanical properties of the nanocomposites were observed from tensile test.From this research,a possible exfoliation of silicate layered of Cloisite B30 in the PLA matrix was demonstrated as there were no noticeable XRD peaks was observed.SEM images could not determine the nanoclay dispersion but the nanocomposite samples possessed large aggregates,whose role as stress concentrators.In thermal analysis,TGA resulted in the decrease of thermal stability with increasing loading of Cloisite B30.The glass transition temperature for the nanocomposites also has no improvement on Tg compared to pure PLA. Mechanical analysis of the nanocomposites was studied using Universal Testing Machine. A poor ultimate stress and ultimate strength but more elasticity of nanocomposites was observed compared to pure PLA.